Roles of serum and biliary CEA, CA19-9, VEGFR3, and TAC in differentiating between malignant and benign biliary obstructions - İnce, Ali Tüzün; Yıldız, Kemal; Baysal, Birol; Danalıoğlu, Ahmet; Kocaman, Orhan; Tozlu, Mukaddes; Gangarapu, Venkatanarayana; Sarbay Kemik, Ahu; Uysal, Ömer; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Despite the presence of many diagnostic methods, the differential diagnosis between benign and malignant biliary obstructions is still not easy. We aimed to evaluate the role of serum/biliary carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9), vascular endothelial growth factor receptor-3(VEGFR-3), and total antioxidant capacity (TAC) tests in this differential diagnosis. Materials and Methods: Patients (n:225; 110♂, 115♀) with diagnosis of malignant (n:96) or benign (n:129) biliary obstruction were included in this cross-sectional study. Serum and biliary CEA, CA 19-9, VEGFR-3, and TAC tests were analyzed, statistics were obtained, and significance was defined as p<0.05. Results: Mean age was 54.9±16.4 for the benign and 54.2±19.6 for the malignant group (p=0.89). Head of pancreas cancer (18.2%), cholangiocarcinoma (11.4%) and choledochal stone (48%) were the most common etiologies. The area under the curve (AUC)s by ROC analysis of serum/biliary CA 19-9, VEGFR-3, and TAC and serum CEA were 0.701/0.616, 0.622/0.663, 0.602/0.581, and 0713, respectively. Serum TAC had higher sensitivity (61.1%) and CEA had lower sensitivity (42.7%), whereas CEA had higher specificity (89.9%) and TAC had lower specificity (60.5%). In biliary tumor markers, CA 19-9 had higher sensitivity (74%) and VEGFR-3 had lower sensitivity (56.2%); however, VEGFR-3 had higher specificity (79.1%) and CA 19-9 had lower specificity (34.1%). Additionally, combination of serum CEA (p<0.001), CA 19-9 (p<0.001), VEGFR-3 (p<0.001), and biliary CA 19-9 (p=0.028) markers achieved 95% estimation probability, and the sensitivity, specificity, and accuracy were 88.5%, 45.7%, and 64%, respectively. Conclusion: Serum and biliary CEA, CA 19-9, VEGFR-3, and TAC tests would not be useful in the differentiation between malignant and benign biliary obstructions.